A critical review on formulations used in the management of prameha (diabetes) from various compendia - Kirti Chaudhari, Pramod Khobragade, Pooja Chaudhari, Vaishali Datir, Shubhada Gade , Dattu Hawale (Drugs and Cell Therapies in Hematology, 2021)
Prameha is a metabolic disorder characterized by excessive urination, both in quantity as well as frequency. It can be co- related with Diabetes mellitus of modern science. The urine appears turbid in this disease. Prameha is classified into 3 main types as per the Ayurvedic classics-Vataj, Pittaj, Kaphaj Prameha. There are 4 Vataj, 6 Pittaj and 10 Kaphaj Prameha. This review work is an attempt to compile and present Prameha management in systematic manner with scientific observations from Ayurvedic classical texts. In present study, different formulations were compiled from 4 different compendia, which are indicated for the management of Prameha. Ayurvedic treatment of the disease will help the person to prevent serious complications of diabetes with minimal drug induced side effects, if administered in proper way. Various ayurvedic drugs used in these formulations are known to have anti diabetic, anti hyperlipidaemic, antioxidant and immuno - modulatory activities.